2017
DOI: 10.1074/jbc.m117.781906
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution three-dimensional NMR structure of the KRAS proto-oncogene promoter reveals key features of a G-quadruplex involved in transcriptional regulation

Abstract: Non-canonical base pairing within guanine-rich DNA and RNA sequences can produce G-quartets, whose stacking leads to the formation of a G-quadruplex (G4). G4s can coexist with canonical duplex DNA in the human genome and have been suggested to suppress gene transcription, and much attention has therefore focused on studying G4s in promotor regions of disease-related genes. For example, the human proto-oncogene contains a nuclease-hypersensitive element located upstream of the major transcription start site. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 84 publications
5
48
0
Order By: Relevance
“…The structure of the quadruplex in the KRAS promoter is polymorphic, with most conformations containing an atypical single nucleotide bulge ( 18 ). A structure of a G4-forming sequence derived from the KRAS promoter was recently solved by NMR, confirming the proposed structure ( 20 ). Previous studies have provided preliminary evidence that the KRAS G4 can indeed be targeted with small molecules to elicit changes in KRAS expression ( 21–23 ).…”
Section: Introductionsupporting
confidence: 54%
“…The structure of the quadruplex in the KRAS promoter is polymorphic, with most conformations containing an atypical single nucleotide bulge ( 18 ). A structure of a G4-forming sequence derived from the KRAS promoter was recently solved by NMR, confirming the proposed structure ( 20 ). Previous studies have provided preliminary evidence that the KRAS G4 can indeed be targeted with small molecules to elicit changes in KRAS expression ( 21–23 ).…”
Section: Introductionsupporting
confidence: 54%
“…DMS-footprinting and CD experiments showed that 32R folds into a parallel G4 with a thymidine bulge in one strand and a (1/1/11) topology ( 23 , 25 ). Moreover, a truncated portion of 32R, comprising the first four G-runs from the 5′-end, folds into a (1/1/4) G-quadruplex ( 28 , 38 ). We reported that 32R is recognized by several nuclear proteins, including MAZ, PARP-1, Ku70 and hnRNP A1 ( 25 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, neither DC-34-binding site in the MYC G4 is obscured by residues from the loop regions, whereas other G4s that we examined have features that make the DC-34 binding sites less accessible. We generated a model of a KRAS G4/DC-34 structure using the KRAS G4 structure (PDB 5I2V) 61 with DC-34 placed in the analogous region compared to its MYC -binding sites. At the 5′ end, the KRAS G4 contains a four-base loop (A14-A15-T16-A17) while the MYC G4 has a one base loop (T19) (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%